A Review of the User Fees Policy for Primary Healthcare Consultations in Botswana: Problems With Effective Planning, Implementation and Evaluation - Vincent Pagiwa; Alan Shiell; Simon Barraclough; Onalenna Seitio-Kgokgwe (Kerman University of Medical Sciences, 2022)
Background  The Government of Botswana introduced user-fees for primary healthcare consultations in 1975. The policy has remained in place since then, although the fee has remained largely unaltered despite rising inflation. Early reviews of the policy pointed to problems in its implementation, but there has been no evaluation in the past 20 years. The aim of this study was to review the policy to assess whether documented issues with its implementation have been addressed. Methods  This qualitative study involved interviews with 32 key informants: 18 policy-makers and 14 front-line revenue collectors. Data were analysed thematically using a template approach with constructs from an established organizational capacity assessment framework used as predetermined categories to guide data collection and analysis. Results  Limited administrative and management capacity has been a major hindrance to effective implementation of the policy. The lack of infrastructure for effective revenue collection led to misappropriation of funds. Lack of clear guidelines for health facilities on how to implement the policy generated interdepartmental conflicts. Study participants believed the current policy was unlikely to be cost-effective since the cost of collecting fees probably exceeded the revenue it generated.Conclusion  If the Botswana Government persists with the policy then it needs to improve organizational capacity to collect and manage revenues efficiently. However, policy thinking since the turn of the century has turned away from user-charges in healthcare as they impede the move towards universal access. It is timely therefore to consider alternative financing approaches that are more effective and a more equitable means of paying for healthcare.